2008
DOI: 10.1007/s12041-008-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to different climates results in divergent phenotypic plasticity of wing size and shape in an invasive drosophilid

Abstract: The phenotypic plasticity of wing size and wing shape of Zaprionus indianus was investigated in relation to growth temperature (17 degrees C to 31 degrees C) in two natural populations living under different climates, equatorial and subtropical. The two populations were clearly distinguished not only by their wing size (the populations from the colder climate being bigger in size), but also by the shape of the response curves to growth temperature i.e., their reaction norms. In this respect, the temperature at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 51 publications
3
24
1
1
Order By: Relevance
“…Shape changes independent of size variation have been found in several studies in different Drosophila species and by means of different analytical approaches (Weber 1992, Bitner-Mathé & Klaczko 1999, Hoffmann & Shirriffs 2002, Kjaersgaard et al 2007, and there is some evidence that wing shape is related to fitness (Cavicchi et al 1991, Kölliker-Ott et al 2003, Carreira et al 2006. A decrease in wing aspect with temperature has usually been found in line with the theoretical expectations (Hoffmann & Shirriffs 2002, Santos et al 2006, Loh et al 2008, but see Gilchrist et al 2000) but apparently parallel selection is not operating among different Drosophila species (Loeschcke et al 1999, 2000, Gilchrist et al 2000, Hoffmann & Shirriffs 2002. The reduction in wing size with temperature often does not merely reflect linear scaling with overall structural size.…”
Section: Introductionmentioning
confidence: 52%
“…Shape changes independent of size variation have been found in several studies in different Drosophila species and by means of different analytical approaches (Weber 1992, Bitner-Mathé & Klaczko 1999, Hoffmann & Shirriffs 2002, Kjaersgaard et al 2007, and there is some evidence that wing shape is related to fitness (Cavicchi et al 1991, Kölliker-Ott et al 2003, Carreira et al 2006. A decrease in wing aspect with temperature has usually been found in line with the theoretical expectations (Hoffmann & Shirriffs 2002, Santos et al 2006, Loh et al 2008, but see Gilchrist et al 2000) but apparently parallel selection is not operating among different Drosophila species (Loeschcke et al 1999, 2000, Gilchrist et al 2000, Hoffmann & Shirriffs 2002. The reduction in wing size with temperature often does not merely reflect linear scaling with overall structural size.…”
Section: Introductionmentioning
confidence: 52%
“…This is the first study on variability of wing size of a Chilean lepidopteran. The plasticity response could explain this pattern, where growth and available energy (temperature) or other vital elements (water) in combination with the time available to complete development produce a decrease in development at low temperatures in high altitude sites (Loh et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of chromosomal inversion carried out by Ananina et al (2007) also revealed five new inversions in Brazilian populations, which were therefore found to be more polymorphic than Indian populations. High variability was also observed in wing size and shape in relation to growth temperature in two natural populations, Rio de Janeiro, Brazil, and São Tomé Island, near Africa (Loh et al, 2008). Low variability was only found in Santa Cruz da Esperança, SP.…”
Section: Discussionmentioning
confidence: 84%
“…Investigations have been made of colonization dynamics and genetic variability of Z. indianus populations in Brazil, including several studies using genetic markers such as allozymes (Mattos-Machado et al, 2005), chromosomal inversion polymorphisms (Ananina et al, 2007), and quantitative traits (David et al, 2006;Loh et al, 2008). Ours is, to the best of our knowledge, the first study of genetic variability of Z. indianus Brazilian populations based only on molecular markers.…”
Section: Discussionmentioning
confidence: 99%